An Intelligent Approach Based Embedded System Design For Telemedicine Application - Narayan Mohanty, Mihir (Ingeniería Solidaria, 2018)
Introduction: The present research was conducted at Sikha ‘O’ Anusandan (deemed to be University) in 2017. Telemedicine application in the field of medicine creates a new age. Accordingly, it requires technology to be compatible. Easy access and fast processing are the major focuses in different applications. In this paper, an approach has been considered to diagnose heart diseases. Methods: The model is designed using fuzzy logic in which the rule-based principle is applied to satisfy the objective. The model is developed keeping a view over the multi-agent system. The diagnosis of the patient is performed using Fuzzy Inference System (fis). Results: The pathological test results will help to form the rules of the model and can work for the diagnosis in a convenient way. Furthermore, the results of detection are communicated through Internet and sms for monitoring and post care purpose of supporting IoT application. Conclusion: The simulated result shows its performance can be helpful to physicians as well as patients from remote places. Originality: The model is proposed for disease detection and monitoring patients on remote locations. Also, distributed agents are proposed to act on a common platform using Internet for the benefit of society. This will save time for physicians and travelling costs for the patient. Limitations: The research results can be practically implemented in new medical equipment for hospitals with earlier equipment.